Pengaruh Pemberian Gel Doksisiklin terhadap Jumlah Makrofag pada Proses Penyembuhan Dermatitis Paederus akibat Racun Tomcat (Paederus sp.) pada Mencit (The Effect of Doxycycline Gel Application toward the Number of Macrophage in Dermatitis Paederus He - Bagus Indra Kusuma; Al Munawir; Septa Surya Wahyudi (Pustaka Kesehatan, 2016)
Paederus dermatitis is an acute skin irritation caused by skin contact with toxins in the rove beetle (Paederus sp). Pederin poison was previously thought derived from the rove beetle's body. Based on other studies, poison pederin obtain from the symbiotic rove beetles and Pseudomonas aeruginosa which is able to secrete the matrix metalloprotease (MMP). Doxycycline is an antibiotic act as an inhibitor of MMP. This study aimed to verify the effect of Doxycycline gel to the number of macrophages in healing process Paederus dermatitis due to poison of rove beetle (Paederus sp.). The study design was a quasy experimental design using 40 mice (Mus musculus), were divided into 4 groups. Normal control group, negative control group, P1 group was given doxycycline 1%, and P2 group was given doxycycline 5%. Experimental animals were terminated on day 1, 3, 5, 7, and 15. The result of One Way Annova test on the number of macrophages on day 1, 3 and 5 showed a significance of 0.00 (p<0.05). This study showed that there was a significant difference in the effect of doxycycline gel to the number of macrophages in healing process of Paederus dermatitis. Keywords: dermatitis paederus, doxycycline gel, macrophages